Resource recovery and reuse as an incentive for a more viable sanitation service chain - Rao, Krishna C.; Otoo, Miriam; Drechsel, Pay; Hanjra, Munir A. (2017)
Recovering nutrients, water and energy from domestic waste streams, including wastewater and faecal sludge, is slowly gaining momentum in low-income countries. Resource recovery and reuse (RRR) offers value beyond environmental benefits through cost recovery. An expected game changer in sanitation service provision is a business model where benefits accrued via RRR can support upstream sanitation services despite the multitude of private and public stakeholders involved from waste collection to treatment. This paper shows options of how resource recovery and reuse can be an incentive for the sustainable sanitation service chain, by recovering costs where revenue can feed back internally or using generated revenues from reuse to fill financial gaps across the service chain to complement other supporting mechanisms for making waste management more attractive.